Ignoring personal moral compass: factors shaping bankers' decisions. Issue 3 (8th July 2019) - Thiam, Mouhamed El Bachire; Liu, Jonathan; Aston, John
Abstract : Purpose: The purpose of this paper is to increase our understanding of the challenges the banking industry continues to face from an ethics standpoint more than a decade after the credit crisis. Since 2007, there has been renewed interest in the way professional ethics is integrated within the banking culture. With a public that has become more sensitive towards ethical and corporate governance failures, the banking industry has been at the receiving end of strong ethical criticism. Yet, in spite of the regulatory response to the crisis, ethics is still a major issue in an industry where the corporate governance systems implemented by companies have failed to control employee behaviours, even in institutions branding themselves as ethical banks. Design/methodology/approach: This paper studies factors inside and around institutions in the banking industry that impact the moral anomie in bankers' professional environment. This paper applies an ordinary least square regression analysis, preceded by exploratory and confirmatory factor analysis, to test the hypothesised relations between anomie and the factors proposed. Findings: The results show that long-term orientation, strategic aggressiveness and competitive intensity do have an influence on anomie. These results are compared to previous research applied in non-financial industries and prompt the strengthening of corporate governance systems in financial companies with aggressive corporate cultures. Originality/value: The paper therefore introduces the factors that lead bankers to ignore the morals they gained from society and provide a better understanding of the reasons behind the deviant behaviours that caused the crisis a decade ago. It represents a crucial first step for future policymaking that fills an important gap in the financial regulation literature. Indeed, the lack of understanding of the factors dictating behaviours in the industry meant that regulatory changes in the past decade have mostly focussed on technical aspects of the problem (e.g. new capital structure requirements) and produced few answers to address the ethical challenges.